Assessment of the quality of life in children and adolescents with asthma - Duška Jovič; Snežana Petrović-Tepić; Darija Kneževic (Nurses and Midwives Association of Slovenia, 2018)
Introduction: Asthma is a global health problem that negatively affects various aspects of the quality of a person's life. The aim of the study was to examine the quality of life in children and adolescents with asthma and the correlation between the degree of asthma control and the quality of life. Methods: The cross-sectional study included 100 children and adolescents with asthma over a six-month period in 2015. The study used: Standardized Pediatric Asthma Quality of Life Questionnaire (PAQLQ(S)) for the assessment quality of life and the questionnaires for the assessment of asthma control for two age groups: Asthma Control Test (ACT) for adolescents and Childhood Asthma Control Test (C-ACT). Results: 62 boys and 38 girls aged 7−17, whose average age was 11.2 (s = 2.7) years were included in the study. The overall PAQLQ(S) score ranged between 3.30 and 7.00 with an average mean value of 5.95. The findings have showed that most children with asthma estimated their overall PAQLQ(S) on the positive end of the scale. The children reported more impairment in the domain of 'Emotion' ( = 5.84) than in 'Activities' and 'Symptoms'. The percentage of adolescents in the category of poor control (12.5 %) was significantly lower than in the group of children (25.0 %). In both groups of children, the sub-scale 'Symptoms' was in highest correlation with the degree of asthma control (r = 0.915, p < 0.01). Discussion and conclusion: In this study the children and adolescents with asthma showed an overall good quality of life. Control of asthma symptoms in children and adolescents positively influenced their quality of life.